Clinical feasibility of endoscopic submucosal dissection with minimum lateral margin of superficial esophageal squamous cell carcinoma - Kuwabara, Hiroki; Abe, Seiichiro; Nonaka, Satoru; Suzuki, Haruhisa; Yoshinaga, Shigetaka; Oda, Ichiro; Saito, Yutaka (Endoscopy International Open, 2019)
Background Esophageal stricture following endoscopic submucosal dissection (ESD) for superficial esophageal squamous cell cancer (SESCC) has been associated with wide mucosal defects greater than three-quarters of the luminal circumference. Some patients developed dysphagia and required repeated endoscopic balloon dilation even after steroid therapy. As iodine staining clearly visualized the margin of SESCC, we made a longitudinal mucosal incision close to the margin of the lesion to avoid a mucosal defect involving over three-quarters of the luminal circumference for large lesions. This retrospective study aimed to clarify the clinical feasibility of ESD with minimum lateral margin of SESCC.Patients and methods Between 2005 and 2013, 94 patients with 94 initial SESCCs had lesions greater than half of the luminal circumference. Of those, 70 patients with 70 SESCCs had achieved endoscopic clearance for the initial SESCC. In this study, endoscopic clearance was defined as en bloc resection of SESCC histologically confined to the mucosa without lymphovascular invasion and with a free deep margin regardless of the lateral margin. This study evaluated the short- and long-term outcomes in patients undergoing endoscopic clearance.Results In total, 61.4 % (43/70) of the patients had mucosal defects involving over three-quarters of the luminal circumference and 38.5 % (27/70) had a positive or indeterminate lateral margin. However, there was no local or nodal recurrence during the median follow-up period of 3.8 years; the 3-year overall survival rate was 98.5 % and the 3-year disease-free survival rate was 100 %.Conclusion Using our institutions’ strategy, ESD for SESCCs with minimum lateral margins was oncologically acceptable; this approach could reduce the known risk factor of post-ESD stricture.